UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN KEPERCAYAAN DIRI PESERTA DIDIK MELALUI MODEL DISCOVERY LEARNING - Aisah, Siti; Achmad Mudrikah; Sulastri, Yayu Laila (Universitas Islam Nusantara, 2024)
This research was motivated by the low mathematical problem solving abilities and self-confidence of students in learning mathematics in Class VII A MTs Al-Falah Jatinangor. One alternative solution is to apply the Discovery Learning learning model. The purpose of this research is to determine the increase in students' mathematical problem solving abilities after using the Discovery Learning learning model and to determine the increase in students' self-confidence after using the Discovery Learning learning model. The method used is the classroom action research method (PTK), which is carried out in 2 cycles consisting of planning, action implementation, observation and reflection. The data taken is qualitative data, namely data from teacher observations, self-confidence questionnaires and students' daily journals. As well as quantitative data, namely learning outcome data obtained from the results of mathematical problem solving ability tests. The data obtained was analyzed using percentages. From the results of data analysis, it was concluded that students' mathematical problem solving abilities and self-confidence increased after learning using the Discovery Learning model. Keywords: Discovery-Learning Model, Problem Solving Skill, Self-Confidence